A conservative pathway for coordination of cell wall biosynthesis and cell cycle progression in plants. (23rd March 2021) - Shi, Jiewei; Zhang, Qunxia; Yan, Xu; Zhang, Delin; Zhou, Qin; Shen, Yuxiao; Anupol, Nachaisin; Wang, Xiuqing; Bao, Manzhu; Larkin, Robert M.; Luo, Hong; Ning, Guogui
Summary: The mechanism that coordinates cell growth and cell cycle progression remains poorly understood; in particular, whether the cell cycle and cell wall biosynthesis are coordinated remains unclear. Recently, cell wall biosynthesis and cell cycle progression were reported to respond to wounding. Nonetheless, no genes are reported to synchronize the biosynthesis of the cell wall and the cell cycle. Here, we report that wounding induces the expression of genes associated with cell wall biosynthesis and the cell cycle, and that two genes, AtMYB46 in Arabidopsis thaliana and RrMYB18 in Rosa rugosa, are induced by wounding. We found that AtMYB46 and RrMYB18 promote the biosynthesis of the cell wall by upregulating the expression of cell wall‐associated genes, and that both of them also upregulate the expression of a battery of genes associated with cell cycle progression. Ultimately, this response leads to the development of curled leaves of reduced size. We also found that the coordination of cell wall biosynthesis and cell cycle progression by AtMYB46 and RrMYB18 is evolutionarily conservative in multiple species. In accordance with wounding promoting cell regeneration by regulating the cell cycle, these findings also provide novel insight into the coordination between cell growth and cell cycle progression and a method for producing miniature plants. Significance Statement: How the cell growth and cell cycle progression are coordinated still is one of the remaining great conundrums.Whether there is an interplay between cell cycle and cell wall synthesis is remain unclear. To clarify the relationship between cell growth and cell cycle will be of great significance for rational manipulation of plant growth and shape. Here, we report two wounded‐induced transcription factors, AtMYB46 in Arabidopsis thaliana and RrMYB18 in Rosa rugos a, promote the biosynthesis of the cell wall by up‐regulating the expression of cell wall associated genes, and also up‐regulate the expression of a battery of genes associated with cell cycle progression. Ultimately, this response leads to the change of plant growth and shape. We also found that the coordination of cell wall biosynthesis and cell cycle progression is evolutionarily conservative in multiple species. These findings provide novel insight into the coordination between cell growth and cell cycle progression and a method for producing miniature plants.